The influence of anisotropic voxel caused by field of view setting on the accuracy of three-dimensional reconstruction of bone geometric models - Yaming Liu; Ruining Li; Yuxuan Fan; Ðorđe Antonijević; Petar Milenković; Zhiyu Li; Marija Djuric; Yifang Fan (AIP Advances, 2018)
The finite element method is playing an increasingly important role in osteoporosis screening. An accurate bone geometric model, a prerequisite for the finite element analysis, is affected by voxels. Isotropic voxel has advantages in three-dimensional reconstruction, but field of view setting usually results in anisotropic voxels. The main goal of this study was to investigate the influence of anisotropic voxel on the accuracy of three-dimensional reconstruction of bone geometric models. Sixty metatarsal bones were scanned twice with an interval of 18 months with different fields of view. We reconstructed these metatarsals and compared them. The results showed that there was no significant difference in volume, surface, length, width and height and two principal moments of inertia, indicating that anisotropic voxel caused by field of view setting has a neglectable effect on the three-dimensional reconstruction of bone geometric models, and that using finite element method based on bone geometric model reconstructed by anisotropic voxel to predict bone strength is reliable.